High‐spatial and high‐temporal resolution dynamic contrast‐enhanced perfusion imaging of the liver with time‐resolved three‐dimensional radial MRI. Issue 3 (20th March 2013) - Brodsky, Ethan K.; Bultman, Eric M.; Johnson, Kevin M.; Horng, Debra E.; Schelman, William R.; Block, Walter F.; Reeder, Scott B.
<x xml:space="preserve">Abstract</x> Purpose Detection, characterization, and monitoring the treatment of hepatocellular carcinomas (HCC) in patients with cirrhosis is challenging because of their variable and rapid arterial enhancement. Multiphase dynamic contrast‐enhanced MRI is used clinically for HCC assessment; however, the method suffers from limited temporal resolution and difficulty in coordinating imaging and breath‐hold timing within a narrow temporal window of interest. In this article, a volumetric, high‐spatial resolution, and high‐temporal resolution dynamic contrast‐enhanced liver imaging method for improved detection and characterization of HCC is demonstrated. Methods A time‐resolved three‐dimensional radial acquisition with iterative sensitivity‐encoding reconstruction images the entire abdomen and thorax with high spatial and temporal resolution, using real‐time three‐dimensional fluoroscopy to match the breath hold to contrast arrival. The sequence was tested on 17 subjects, including eight patients with HCC or other hypervascular focal lesions. Results This technique was successful in acquiring volumetric imaging of the entire liver with 2.1‐mm isotropic spatial and true 4‐s temporal resolution. Conclusion This technique may be suitable for detecting, characterizing, and monitoring the treatment of HCC. It also holds significant potential for perfusion modeling, which may provide a noninvasive means to rapidly determine the efficacy of chemotherapeutic agents in these tumors over the entire liver volume. Magn Reson Med 71:934–941, 2014. © 2013 Wiley Periodicals, Inc.